The Role of the Integrated Law Enforcement Center (Gakkumdu) in Election Crime Enforcement - Handitya, Binov (Law Research Review Quarterly, 2018)
The election is a tangible form of the concept of democracy which is believed to be one of the principles of governance in Indonesia. But in the implementation of the democratic party there were still shortcomings in the journey. One of the factors that cause the rise of money politics is the lack of awareness of most Indonesians that elections are the most effective vehicle for upholding people's sovereignty. For example, the presence of fictitious or fake voices often colors the event of a democratic party in this country. People are not aware that the various events that emerged earlier can be categorized as election crimes whose threat of sanctions has been firm. In Act No. 7 of 2017 concerning Election shows the seriousness of the government in combating election crime through the formation of Gakkumdu. Gakkumdu as an integrated law enforcement center has an important role in handling election crimes. In Article 486 item (1) of Law No. 7 of 2017 explicitly explained the formation of Gakkumdu intends to equalize the understanding and pattern of handling election crimes by the Bawaslu, the Indonesian National Police, and the Attorney General's Office of the Republic of Indonesia. The topic of the problem that will be discussed in this article is the role of Gakkumdu in suppressing election crimes in the Presidential elections in the 2019 Election.